2015
DOI: 10.5888/pcd12.150065
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Neighborhood Food Environments: Distance Traveled to Food Establishments in 5 US Cities, 2009–2011

Abstract: IntroductionAccurate conceptualizations of neighborhood environments are important in the design of policies and programs aiming to improve access to healthy food. Neighborhood environments are often defined by administrative units or buffers around points of interest. An individual may eat and shop for food within or outside these areas, which may not reflect accessibility of food establishments. This article examines the relevance of different definitions of food environments.MethodsWe collected data on trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…In investigating this issue, many studies have shown significant associations between the neighborhood food environment, diet and obesity (Caspi et al, 2012; Morland and Everson, 2009; Wang et al, 2007); however, many other have suggested that no significant relationship exists (Hattori et al, 2013). Inconsistencies between findings could perhaps be due to how neighborhood and local food environments have been defined (Liu et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In investigating this issue, many studies have shown significant associations between the neighborhood food environment, diet and obesity (Caspi et al, 2012; Morland and Everson, 2009; Wang et al, 2007); however, many other have suggested that no significant relationship exists (Hattori et al, 2013). Inconsistencies between findings could perhaps be due to how neighborhood and local food environments have been defined (Liu et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Less discussed is the choice of appropriate “neighborhood” boundaries or scale and the geographic context in which to operationalize food environment data (Liu et al, 2015; Fan et al, 2014; Larson et al, 2009). Many geographical boundaries have been used to define neighborhood food environments, ranging from egocentric buffer distances of 100 meters to 2.5 kilometers (~1.6 miles) around individual residential, worksite or school addresses or using administrative-based units, e.g., census tracts or block groups (Liu et al, 2015; Fan et al, 2014; Caspi et al, 2012; Charreire et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Labrecque et al 2016;Ji and Wood 2007;Verplanken and Wood 2006;Wood and Neal 2009;). Experience sampling research shows, for example, that approximately 43% of a consumer's actions are performed daily, often in the same context (Wood, Tam, and Witt 2002; see also Liu, Han, and Cohen 2015). Consumers tend to buy the same brands, purchase similar amounts across shopping episodes, and consume similar types of food at mealtimes (for a discussion, see Wood and Neal 2009).…”
mentioning
confidence: 99%